2013
DOI: 10.1177/1357633x13490901
|View full text |Cite
|
Sign up to set email alerts
|

Video telehealth for weight maintenance of African-American women

Abstract: Summary We evaluated the effect of home telehealth on weight maintenance after a group-based weight loss programme. The home telehealth intervention comprised telephone counselling and home Internet-enabled digital video recorders (DVRs) with three channels of video programmes. The video content provided reinforcement and support to promote problem solving, prevent relapse, and sustain motivation. Eighty-eight obese or overweight African-American women were randomized to receive monthly telephone counselling (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 15 publications
0
48
0
Order By: Relevance
“…22 Common inclusion criteria included overweight or obesity 15,18,26,32,34,36,37 and sedentary. 17,22,29,31,33,36,38–40 Few studies focused on women who were age 40 or older 19,25 and age 60 or older.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Common inclusion criteria included overweight or obesity 15,18,26,32,34,36,37 and sedentary. 17,22,29,31,33,36,38–40 Few studies focused on women who were age 40 or older 19,25 and age 60 or older.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies 11,14,17,18,21,24,25,27,34,38,39,43–45 included group exercise sessions. This review revealed that several studies included a group meeting or educational session.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings underscoring the effectiveness of video-based media were observed in different settings. [15][16][17][18] The common themes observed were that video alternatives offer alternative perspectives and approaches to information acquisition. These displays have a tendency to accentuate key points through animation or overemphasis that appear to be vital to future recall.…”
Section: Discussionmentioning
confidence: 99%
“…62 When home video telehealth and monthly telephone counseling, respectively, were used to maintain weight in African-American women, there were no differences in outcomes for the two methods; however, valid digital video recorder use during the intervention period was reported as low, ranging from zero to 42% use per participant. 63 In an 18-month longitudinal study of telehealth for diabetes management, patients using telehealth required less support in physical activity, healthy eating, and problem-solving behaviors than control participants, but more support in medication adherence and healthy coping. 64 It might be that telehealth users became dependent on telehealth to promote medication adherence and provide coping advice.…”
Section: Forming Communities Of Knowledge and Practicementioning
confidence: 99%